2022
DOI: 10.3389/fphy.2022.963716
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-bond networks for proton couplings in G-Protein coupled receptors

Abstract: G-protein signaling pathways mediate communication across cell membranes. The first steps of this communication occur at the cell membrane, where upon receiving an external signal –the binding of an agonist ligand– the membrane-embedded G-Protein Coupled Receptor adopts a conformation recognized by a cytoplasmatic G protein. Whereas specialized GPCRs sense protons from the extracellular milieu, thus acting as pH sensors in specialized cells, accumulating evidence suggests that pH sensitivity might be common to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
1
2
0
Order By: Relevance
“…Our hypothesis is that dynamic water-mediated H-bond networks are central to such long-distance coupling. This hypothesis is compatible with the key role of internal water molecules and water-mediated H-bond networks in proton transporter function [44] , [45] , [46] , [47] and GPCR activation [48] , [49] , [50] , [51] , [52] .…”
Section: Introductionsupporting
confidence: 79%
“…Our hypothesis is that dynamic water-mediated H-bond networks are central to such long-distance coupling. This hypothesis is compatible with the key role of internal water molecules and water-mediated H-bond networks in proton transporter function [44] , [45] , [46] , [47] and GPCR activation [48] , [49] , [50] , [51] , [52] .…”
Section: Introductionsupporting
confidence: 79%
“…22 For some GPCRs, the protonation states of ionizable residues displayed to affect the conformational states as shown by several studies. [23][24][25][26][27] However, to our knowledge the effects of ionizable critical residues of CCR5 was not considered in detail for its conformational heterogeneity.…”
mentioning
confidence: 99%
“…Previous studies on GPCRs indicated the effects of pH and ionization state of certain residues on active/inactive state of the receptor as already mentioned in previous paragraph. [23][24][25][26][27] Hence, it is intriguing to study the possible effect of the protonation state of a binding site residue GLU283 7.39 , whether it could lead to conformational differences especially when CCR5 is in complex with different binding partners. The protonation state of this residue could also have impacts on the design of novel CCR5 inhibitor as it is illustrated that different ligands could lead to titratable residues to be in different protonation states.…”
mentioning
confidence: 99%